Stratified Bacterial Diversity along Physico-chemical Gradients in High-Altitude Modern Stromatolites - Toneatti, Diego M.; Albarracín, Virginia H.; Flores, Maria R.; Polerecky, Lubos; Farías, María E. (Frontiers in Microbiology, 2017)
At an altitude of 3,570 m, the volcanic lake Socompa in the Argentinean Andes is presently the highest site where actively forming stromatolite-like structures have been reported. Interestingly, pigment and microsensor analyses performed through the different layers of the stromatolites (50mm-deep) showed steep vertical gradients of light and oxygen, hydrogen sulfide and pH in the porewater. Given the relatively good characterization of these physico-chemical gradients, the aim of this follow-up work was to specifically address how the bacterial diversity stratified along the top six layers of the stromatolites which seems the most metabolically important and diversified zone of the whole microbial community. We herein discussed how, in only 7 mm, a drastic succession of metabolic adaptations ocurred: i.e. microbial communities shift from a UV-high/oxic world to an IR-low/anoxic/high H2S environment which force stratification and metabolic specialization of the bacterial community, thus, modulating the chemical faces of the Socompa stromatolites. The oxic zone was dominated by Deinococcus sp. at top surface (0.3 mm), followed by a second layer of Microcoleus sp. (0.3 to ~ 2 mm). Sequences from anoxygenic phototrophic Alphaproteobacteria, along with an increasing diversity of Bacteroidetes, Spirochaetes, and other minor represented phyla were found at middle layers 3 and 4. Deeper layers (5 to 7 mm) were mostly occupied by sulfate reducers of Deltaproteobacteria, Bacteroidetes and Firmicutes, next to a high diversity and equitable community of rare, unclassified and candidate phyla. This analysis showed how microbial communities stratified in a physicochemical vertical profile and according to the light source. It also gives an insight of which bacterial metabolic capabilities might operate and produce a microbial cooperative strategy to thrive in one of the most extreme environment on Earth.